Economic Geography and the Location of TNCs: Financial and Professional Service FDI to the USA - Nachum, Lilach (Journal of International Business Studies, 2000)
This paper attempts to examine theoretically and empirically the explanatory power of concepts drawn from economic geography for the explanation of the location of TNCs. It combines concepts from economic geography and international business theories in a model that seeks to explain the location of Transnational Corporations (TNCs), and tests the model on financial and professional service FDI to the US. The findings suggest a need to extend the conventional location model of international business by acknowledging the processes taking place among firms located in geographic proximity.